Reich And Daccord, Best Ideas For Teaching With Technology - A Practical Guide For Teachers, By Teachers - Cumo, Christopher (Teaching History: A Journal of Methods, 2009)
Part roundup of websites, part manual for the use of computer applications in the classroom, Justin Reich and Thomas Daccord's Best Ideas for Teaching with Technology: A Practical Guide for Teachers, by Teachers is, as the title acknowledges, a practical work . Coauthors Reich and Daccord co-direct the website www.EdTechTeacher.org. The two offer workshops for teachers and consulting services for schools. Their experience using computer applications in the classroom qualified them to write this book. Reich has taught world history and topics in modern history at Noble and Greenough School in Dedham, Massachusetts, and has designed courses with a computer-applications component. He is a doctoral candidate at the Harvard Graduate School of Education. Daccord is the author of The Best History Web Sites, and he taught seven years in a school where students and staff had laptops and wireless access to the Internet.